Die Zinsschranke - eine beispiellose Steuerinnovation - Stefan Homburg (Finanz-Rundschau, 2007)
The article deals with the earnings stripping rule (or interest barrier), an important part of the German company tax act 2008. The new rule is analyzed both from an economic and a legal perspective.
Keywords: H25; 330; Corporate taxation; Earnings stripping rule; Corporate taxation; earnings stripping rule